Pelatihan Aplikasi Pupuk Mikoriza pada Lahan Sayuran Kelompok Tani Desa Karangsari Kabupaten Kuningan Jawa Barat - Dede Kosasih; Ika Karyaningsih; Dea Lestari; Fawaz Fauzi Al Rafi; Ai Nurlaila (Journal of Innovation and Sustainable Empowerment, 2025)
Farmers in Karangsari Village have limited access to subsidized fertilizers because they are constrained by the requirements that must be met. This condition encourages farmers to look for alternative fertilizers that can reduce dependence on subsidized fertilizers, one of which is by using mycorrhizal biofertilizers. This service activity is an advanced stage of the previous service activity. The purpose of the activity is to provide training in making plant plots and techniques for using mycorrhizal biofertilizers in the plant cultivation process. Service activities are carried out by lecture and practice methods with stages: 1) pre-test, 2) exposure of fertilizer material, fertilization and biofertilizer (material repetition), 3) practice of making plant demplots, 4) practice of mycorrhizal biofertilizer application to plants, 5) post test, and 6) assistance in plant observation and maintenance. The results of the service show that there is an increase in farmers' knowledge in understanding biological fertilizers and an increase in farmers' awareness/desire in applying biological fertilizers in cultivation practices.